Immune response of Senegalese sole and gilthead seabream after vaccination with an inactivated vaccine against betanodavirus. - Gémez-Mata, Juan; Leiva-Rebollo, Rocío; Moreno-García, Patricia; Bandín Matos, Isabel; Borrego-García, Juan José; Labella Vera, Alejandro Manuel; Castro-López, María Dolores (My University, 2024)
Nervous necrosis virus (NNV) (genus Betanodavirus, family Nodaviridae) is the etiologic agent of viral encephalopathy and retinopathy (VER). This virus is classified into four species: SJNNV, RGNNV, TPNNV and BFNNV. In Southern Europe aquaculture, RGNNV/SJNNV reassortants have been identified in VER outbreaks in Senegalese sole (Solea senegalensis) and gilthead seabream (Sparus aurata). An inactivated vaccine using a reassortant RGNNV/SJNNV isolated from Senegalese sole has been shown to confer partial protection in sole juveniles challenged with the homologous viral strain. In this study, the capacity of the inactivated vaccine to induce Senegalese sole and gilthead seabream immune response has been tested. For this purpose, fish were vaccinated by intraperitoneal injection, and head-kidney and brain samples were obtained at 2, 3 and 7 d post-vaccination (dpv). The evaluation of the immune response was carried out using specific OpenArrays with 56 gene targets for each species. At 2 and 3 dpv, DEGs were mainly up-regulated in both organs analysed in Senegalese sole, whereas in gilthead seabream the down-regulation of DEGs was predominant. The pathway with the greatest up-regulation in Senegalese sole was the type I interferon (IFN-I) system (irf1, irf3, irf7, stat1, isg15, ifit1, and mx). However, in gilthead seabream, the opposite was observed regarding this biological process, as all the genes related to the IFN-I system analysed (tlr3, tlr9, irf1, irf3, irf7, stat1, ifn, mx1, mx2, mx3, isg15, pkr and ifit1) were down-regulated. In addition, receptor-transporting protein 3 (rtp3) was one of the most deregulated gene unrelated to IFN-I response, as has been previously observed after betanodavirus infection in these fish species. Moreover, in each host, rtp3 transcription exhibits the same trend as IFN-I related genes, up-regulation in Senegalese sole and down-regulation in gilthead seabream.
Keywords: Peces - Inmunología; Betanodavirus; Vacuna; Respuesta inmune